A review of the value of human epidermal growth factor receptor 2 (HER2)-targeted therapies in breast cancer. (January 2018) - Nixon, N.A.; Hannouf, M.B.; Verma, S.
Abstract: The cost of cancer drugs continues to escalate with the rapid development and approval of novel therapies, especially over the course of the last decade. In human epidermal growth factor receptor 2 (HER2)-positive breast cancer, the survival benefits gained by new treatments have been undeniably substantial. It is important to assess the financial value of these therapies for decision making at both the societal and individual level. This information is key for managing resources in resource-limited health care systems, while at the same time supporting patient decision-making and conversations between patient and physicians on cost versus benefit. In this article, we perform a systematic review of cost-effectiveness analyses that have been completed to date on HER2-targeted agents, focussing on those that correlate with standard of care therapy. Our discussion also highlights potential strategies to overcome several limitations associated with measuring value for anticancer drugs. Highlights: Targeted therapies HER2-positive breast cancer have provided significant survival benefits, but carry significant costs. A systematic review of cost-effectiveness analyses demonstrates challenges in funding these agents in resource-limited environments. Strategies to reduce overall cost, and improve cost-effectiveness are important to ensure access.